EFFECTIVE TECHNIQUES FOR TEACHING ENGLISH GRAMMAR TO YOUNG LEARNERS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
English has become the most widely studied language globally, largely due to the numerous opportunities it offers to those who are proficient in it. While adults typically encounter fewer challenges in learning English, younger learners often struggle with grammar comprehension. Therefore, it is crucial for educators to understand effective strategies for teaching that cater to the unique needs of these young students.